Perspectives of the work and professional profile of the Public Accountant in Latin America - Lemus Quintero, Jennifer Andrea; Navarro Paba, Astrid (Universidad Francisco de Paula Santander, 2024)
This research article aims to describe the perspectives on the work and professional profile of the Public Accountant in Latin America, focusing on the review of the curricular design of training programs in public higher education institutions in the region. In addition, different technical guidelines led by national and international institutions are reviewed regarding the responses that must be taken into account globally for recovery in post-pandemic times, prioritizing the well-being of people. Documentary research was carried out with a descriptive and qualitative approach, using a deductive method. The results reveal that the professional and work inclinations of Public Accountants after the health crisis address aspects related to the development and improvement of competencies and skills in the management of communication and information technologies, artificial intelligence, environmental and social dimensions. , ethics and social responsibility, active participation in the strategic planning of organizations and teaching and research performance, in light of current labor and legal dynamics